A New Measurement Based on HPB to Measure the Wall Pressure of Electric-Spark-Generated Bubble near the Hemispheric Boundary. (10th February 2020) - Ma, Chunlong; Shi, Dongyan; Cui, Xiongwei; Chen, Yingyu
Abstract : Direct measurement of the wall pressure loading of the spherical boundary subjected to the near-field underwater explosion is a great difficulty. To investigate the wall pressure caused by electric-spark-generated bubble near a hemispheric boundary, an experiment system is developed. In the method of this experiment, a Hopkinson bar (HPB), used as the sensing element, is inserted through the hole drilled on the hemisphere target and the bar's measuring end face lies flush with the loaded face of the hemisphere target to detect and record the pressure loading. The semiconductor strain gauges which stick on Hopkinson bar are used to convert the pressure-based signal to the strain wave signal. The bubble in the experiments is formed by a discharge of 400 V high voltage. To validate the pressure measurement technique based on the HPB, an experimental result from pressure transducer is used as the validating system. To verify the capability of this new methodology and experimental system, a series of electric-spark-generated bubble experiments are conducted. From the recorded pressure-time profiles coupled with the underwater explosion evolution images captured by the high-speed camera (HSV), the shock wave pressure loading and bubble collapse pressure loadings are captured in detail at different dimensionless stand-off distances γ from 0.17 to 2.00. From the results of the experiments conducted in this paper, the proposed experiment system can be used to measure the pressure signal successfully, giving new way to study the bubble collapse pressure when the bubble is near a hemispheric boundary. Through the experimental results, the bubbles generated by different dimensionless stand-off distance γ are divided into four categories, and the bubble load characteristics are also discussed.